STRATEGI PUBLIC RELATION PERUSAHAAN X INDONESIA DALAM MENINGKATKAN CITRA POSITIF - Dasuki, Ira; Trisnawati, Annisa (Jurnal Visi Komunikasi, 2025)
This study wants to answer the Public Relations strategy of Company X Indonesia in improving the company's positive image. The method used in this research is descriptive qualitative.  The theory used in this research is the Model - Two way asymmetrical theory. The research results show that the Public Relations position of a Company From the strategy carried out by Public Relations, it will give rise to responses or opinions from the public in the form of feedback. In its application, Public Relations or Public Relations has various kinds of programs starting with planning or planning to evaluation within the company. Company exploration, by carrying out various positive programs and activities such as CSR programs, providing assistance during the Covid 19 pandemic, as well as scholarships and educational programs for the community, especially exploration areas, as well as collaborating with the government in Indonesia to improve the company's positive image.